2015
DOI: 10.1136/bmjquality.u207871.w4032
|View full text |Cite
|
Sign up to set email alerts
|

Improving the management of sepsis in a district general hospital by implementing the 'Sepsis Six' recommendations

Abstract: Sepsis is a common condition with a major global impact on healthcare resources and expenditure. The Surviving Sepsis Campaign has been vigorous in promoting internationally recognised pathways to improve the management of septic patients and decrease mortality. However, translating recommendations into practice is a challenging and complex task that requires a multi-faceted approach with sustained engagement from local stakeholders.Whilst working at a district general hospital in New Zealand, we were concerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(36 reference statements)
0
15
0
2
Order By: Relevance
“…Other studies of sepsis bundle implementation have yielded mixed results. One study by Kumar et al demonstrated improved compliance to the sepsis six (oxygen, blood cultures, antibiotics, lactate measurement, intravenous fluids, and urine output monitoring) from 29% pre-intervention to 63% post-intervention, but without demonstrable improvement in outcomes [18]. However, most studies indicate improved outcomes even with modest adherence to bundled care [9] [1922].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of sepsis bundle implementation have yielded mixed results. One study by Kumar et al demonstrated improved compliance to the sepsis six (oxygen, blood cultures, antibiotics, lactate measurement, intravenous fluids, and urine output monitoring) from 29% pre-intervention to 63% post-intervention, but without demonstrable improvement in outcomes [18]. However, most studies indicate improved outcomes even with modest adherence to bundled care [9] [1922].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were eligible for the pathway if two or more of the systemic inflammatory response syndrome (SIRS) criteria or a systolic blood pressure of <100 mm Hg were present in a ward setting. Key components of the pathway included establishing intravenous access, drawing two sets of blood cultures prior to administration of antibiotics, and performing venous lactate measurements and a full blood examination (Burrell et al, ; Kumar, Jordan, Caesar, & Miller, ; Mattison, Bilney, Haji‐Michael, & Cooksley, ; Morneau, Chisholm, Tverdek, Bruno, & Toale, ; Box ). Following organisation‐wide education and development of a dedicated checklist for pathway components (embedded in patient medical record), the program was implemented across all wards in March 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Key components of the pathway included establishing intravenous access, drawing two sets of blood cultures prior to administration of antibiotics, and performing venous lactate measurements and a full blood examination Kumar, Jordan, Caesar, & Miller, 2015;Mattison, Bilney, Haji-Michael, & Cooksley, 2016;Morneau, Chisholm, Tverdek, Bruno, & Toale, 2017; Box 1).…”
Section: Development Of Sepsis Pathwaymentioning
confidence: 99%
“…Therefore, SIRS is widely used as part of screening tools for patients at risk of sepsis. SIRS is also often used for case identification in sepsis quality improvement work 7 8…”
Section: Introductionmentioning
confidence: 99%